1991
DOI: 10.1007/bf00282444
|View full text |Cite
|
Sign up to set email alerts
|

A novel phenotype of an excision-repair mutant in Neurospora crassa: Mutagen sensitivity of the mus-18 mutant is specific to UV

Abstract: A UV-sensitive mutant has been isolated from UV-mutagenized conidia of Neurospora crassa. The mutation responsible for the lesion was mapped in linkage group VL, proximal to the nucleolus organizer region. We designated the mutant mus-18. The sensitivity of the mus-18 mutant to UV-irradiation was not particularly high, being less than twice that of the wild-type strain. However, the frequency of mutations at the ad-3 loci induced by UV was extremely high even at low doses, under conditions where survival rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…In addition to repair of UV damage, the NER pathway appears to be necessary for the repair of the chemical adducts since the mus-43 and mus-44 mutants are both sensitive to 4NQO (Fig. 1A), whereas the mus-18 mutant does not exhibit sensitivity (Ishii et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to repair of UV damage, the NER pathway appears to be necessary for the repair of the chemical adducts since the mus-43 and mus-44 mutants are both sensitive to 4NQO (Fig. 1A), whereas the mus-18 mutant does not exhibit sensitivity (Ishii et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…This gene, mus-38, was characterized as a homolog of S. cerevisiae RAD1 (Hatakeyama et al, 1998;Inoue, 1999). Interestingly, N. crassa has another excision repair mechanism for the removal of UVinduced damage that is mediated by the MUS-18 protein (Ishii et al, 1991;Yajima et al, 1995). This protein is a homolog of Schizosaccharomyces pombe UVDE (Yonemasu et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…15 Recently, however, a mutant, designated mus-38, has been shown to be deficient in a gene homologue of the human NER gene, XPF (Ishii and Inoue, unpublished observations). Like the uvde -rad13 -double mutant in S. pombe, a double mutant between mus-18 and mus-38 exhibits a hypersensitivity to UV and fails to remove any UV damage.…”
Section: Uver In N Crassamentioning
confidence: 97%
“…15 The existence of this unique UV-sensitive mutant suggested that a novel UV damage-specific enzyme may be present in N. crassa. Therefore, a cDNA library made from wild-type N. crassa was introduced into Escherichia coli strain SY2 (uvrA recA phr), which is completely deficient in repair of UV damage.…”
Section: A Novel Repair Enzyme For a Novel Excision Repairmentioning
confidence: 99%
See 1 more Smart Citation